2004
DOI: 10.2174/1567205043332225
|View full text |Cite
|
Sign up to set email alerts
|

The Role of P-glycoprotein in Cerebral Amyloid Angiopathy; Implications for the Early Pathogenesis of Alzheimers Disease

Abstract: It has been shown in vitro that beta-amyloid (Abeta) is transported by P-glycoprotein (P-gp). Previously, we demonstrated that Abeta immunoreactivity is significantly elevated in brain tissue of individuals with low expression of P-gp in vascular endothelial cells. These findings led us to hypothesize that P-gp might be involved in the clearance of Abeta in normal aging and particularly in Alzheimer's disease (AD). As we were interested in the early pathogenesis of Abeta deposition, we studied the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 30 publications
9
122
0
3
Order By: Relevance
“…This evidence suggests that accumulation of the toxic form of Aβ can lead to downregulation of the P-glycoprotein 1 transporter. This correlates with human studies that reported elevated levels of Aβ and decreases in P-glycoprotein 1 levels (233,234). The relative contributions to Aβ clearance from capillaries and astrocytes remains to be fully understood.…”
Section: Atp-binding Cassette Transporter Familysupporting
confidence: 87%
“…This evidence suggests that accumulation of the toxic form of Aβ can lead to downregulation of the P-glycoprotein 1 transporter. This correlates with human studies that reported elevated levels of Aβ and decreases in P-glycoprotein 1 levels (233,234). The relative contributions to Aβ clearance from capillaries and astrocytes remains to be fully understood.…”
Section: Atp-binding Cassette Transporter Familysupporting
confidence: 87%
“…This finding, in conjunction with evidence that other ABC family transporters also convey Aβ (12,13,15,16,18), implicates this family of molecules in cerebral Aβ export impairments in AD patients (4). Our results identify ABCC1 in particular as a potential target for impeding the pathogenesis of Aβ proteopathies such as AD and CAA.…”
Section: Discussionmentioning
confidence: 93%
“…The principal known mechanisms that contribute to the elimination of Aβ are degradation (by enzymes, the proteasome complex, and autophagy) (5,6), active, receptormediated transcytotic transport across the blood-brain barrier by LRP1 and RAGE, and by perivascular drainage of the extracellular fluid (7)(8)(9)(10)(11). In addition, 3 members of the ATP-binding cassette transporter family -ABCA1, ABCB1, and ABCG2 -have been shown to export Aβ (12)(13)(14)(15)(16)(17)(18). Members of different ABC transporter subfamilies exhibit different export kinetics for specified substrates (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Ezáltal igazolódott e transzporterek szerepe az amiloid plakkok lerakódásának regulálásában. Több tanulmány igazolta a vér-agy gát endothelsejtjeinek apicalis felszínén a P-gp-expresszió szignifikáns csökkenését a természetes öregedési folyamattal párhuzamosan [55][56][57][58][59]. Mindezen megfigyelések alapján megfontolandó stratégia a P-gp-expresszió fokozása, illetve a transzporter aktiválása az időskori Alzheimer-kór megelőzésében.…”
Section: Alzheimer-kórunclassified